STUDI KASUS CV SABILA MULTI KREASINDO : AKUNTANSI KEPERILAKUAN DALAM BRANDING, PEMBIAYAAN, PERSEPSI PASAR, DAN EKSPANSI UMKM - Cahyaningtyas, Venia; Kurniawan, Faizal Tri; Mabruri, Muhammad; Irfanniah, Zahrotun; Wulandari, Erika (Jurnal Akuntansi Kompetif, 2025)
This research delves into how behavioral accounting aids in comprehending branding strategies, financial choices, market perceptions, and expansion efforts of micro, small, and medium enterprises (MSMEs), particularly through a case study of CV. Sabila Multi Kreasindo, a crafts exporter located in Magelang, Indonesia. The study is driven by the crucial role MSMEs play in bolstering economic progress and international competitiveness, despite challenges with limited resources, branding issues, and uncertainty in decision-making. Employing qualitative research methods like interviews, observations, and documentation, the study reveals that bounded rationality influences decisions such as avoiding bank loans, depending on buyer down payments, and concentrating on Business-to-Business (B2B) marketing. Findings show that rigorous quality control and adaptable risk management reinforce trust-based buyer relationships, while cautious expansion reflects a risk-averse mindset. The study concludes that behavioral accounting provides important insights for developing adaptive strategies, enhancing knowledge on MSME sustainability in global markets.